Risk Factors of Venous Thromboembolism in Noncritically Ill Patients Hospitalized for Acute COVID-19 Pneumonia Receiving Prophylactic-Dose Anticoagulation - Francesco Poletto; Luca Spiezia; Chiara Simion; Elena Campello; Fabio Dalla Valle; Daniela Tormene; Giuseppe Camporese; Paolo Simioni (Viruses, 2022)
Background: Therapeutic/intermediate-dose heparin reduces the risk of thromboembolic events but increases the risk of major bleeding in patients hospitalized for acute COVID-19 pneumonia. Objectives: To prospectively assess the incidence of objectively proven venous thromboembolism (VTE) and identify predisposing risk factors in a cohort of hospitalized patients with acute COVID-19 pneumonia undergoing prophylactic-dose heparin. Patients and methods: All consecutive patients admitted for acute COVID-19 pneumonia to the General Internal Medicine Unit of Padova University Hospital, Italy between November 2020 and April 2021, and undergoing prophylactic-dose heparin, were enrolled. Demographic and clinical characteristics and laboratory and radiological findings were recorded on admission. Cases were patients who developed VTE during their hospital stay. Univariable and multivariable logistic regression analyses were used to ascertain the risk factors associated with developing in-hospital VTE. Results: 208 patients (median age: 77 years; M/F 98/110) were included; 37 (18%) developed in-hospital VTE during a median follow-up of 10 days (IQR, 4–18). VTE patients were significantly younger (p = 0.004), more obese (p = 0.002), and had a lower Padua prediction score (p < 0.03) and reduced PaO2/FIO2 ratio (p < 0.03) vs. controls. Radiological findings of bilateral pulmonary infiltrates were significantly more frequent in VTE patients than controls (p = 0.003). Multivariable regression showed that obesity (1.75, 95% CI 1.02–3.36; p = 0.04) and bilateral pulmonary infiltrates on X-rays (2.39, 95% CI 1.22–5.69; p = 0.04) were correlated with increased risk of in-hospital VTE. Conclusions: Obesity and bilateral pulmonary infiltrates on imaging may help clinicians to identify patients admitted to medical wards for acute COVID-19 pneumonia at risk of developing VTE despite prophylactic-dose heparin. Further studies are needed to evaluate whether the administration of therapeutic/intermediate-dose heparin may help prevent VTE episodes without further increasing the bleeding risk.